2017
DOI: 10.1111/cbdd.13133
|View full text |Cite
|
Sign up to set email alerts
|

Novel 1,3,5‐triazine derivatives exert potent anti‐cervical cancer effects by modulating Bax, Bcl2 and Caspases expression

Abstract: This study aimed to develop novel 1,3,5-triazine derivatives as potent anti-cervical cancer agents. The compounds were synthesized in short steps with an excellent yield and characterized via various spectroscopic and analytical methods. A structure-activity relationship study suggested that electron-withdrawing substituents showed greater anticancer activity than electron-donating groups. Compound 7p (p-fluoro) showed the highest activity against cervical cancer cells. In a nude mouse xenograft model inoculat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 39 publications
(43 reference statements)
0
9
0
Order By: Relevance
“…Bcl-2) or induce (e.g. Bax and caspases) cell death (26). Therefore, the present study detected the protein expression levels of Bcl-2, Bax, caspase-3 and caspase-9.…”
Section: Mir-589-5p Inhibits Viability and Induces Apoptosis Of Prostate Cancer Cellsmentioning
confidence: 81%
“…Bcl-2) or induce (e.g. Bax and caspases) cell death (26). Therefore, the present study detected the protein expression levels of Bcl-2, Bax, caspase-3 and caspase-9.…”
Section: Mir-589-5p Inhibits Viability and Induces Apoptosis Of Prostate Cancer Cellsmentioning
confidence: 81%
“…Regarding the mechanism, Bcl-2 mRNA has been demonstrated to be a direct target of miR-744 in cervical cancer [31]. Bcl-2, an integral protein of the outer mitochondrial membrane, is strongly implicated in the initiation and malignant progression of cervical cancer by regulating cell proliferation, viability, cell cycle progression, apoptosis, epithelial-mesenchymal transition, migration, invasion, and metastasis [39][40][41]. Bcl-2 is reported as a double-edged sword by inducing apoptosis and inhibiting apoptosis at the same time [42,43].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that inhibitors of the autophagy gene ATG4 can inhibit autophagy, enhance the cytotoxicity of chemotherapy drugs, and achieve the purpose of killing tumor cells [ 29 ]. Autophagy gene BCL2 can be used as a therapeutic target of some drugs for cervical cancer [ 30 ]. TM9SF1 can bind to the estrogen receptors, regulate the epithelial-mesenchymal transformation of cancer cells, and promote tumor metastasis [ 31 ].…”
Section: Discussionmentioning
confidence: 99%